Effect of nimodipine and flunarizine on neuromuscular function in mice - Kaikade, Swapnil B.; Pise, Nitin D. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Changes in the intracellular concentration of Ca2+ control a number of cellular and physiological processes, hormone secretion, and cell fate and gene expression. The objective of this study was to study the effect of L-type of calcium channel blocker nimodipine and T-type of calcium channel blocker funarizine on neuromuscular function in mice without pre-treatment by any other drug. Methods: The study was carried out following permission from the Institutional animal ethics committee. Healthy Swiss albino mice of either sex were selected by the strict inclusion and exclusion criteria and the grouping is done. Group A is control treated with normal saline; group B and C received two titrated doses of nimodipine while group D and E received two titrated doses of flunarizine. The animals were then observed for neuromuscular function and the Statistical analysis was done by using unpaired‘t’ test. Results: L-type calcium channel blocker nimodipine has dose dependent effect on locomotor activity on traction wire and while the T- type calcium channel blocker flunarizine has no effect on locomotor activity. Conclusions: Nimodipine has significant dose dependent depressant action on neuromuscular function while flunarizine has no effect on the above mentioned parameter.